2020
DOI: 10.1503/cmaj.200642-f
|View full text |Cite
|
Sign up to set email alerts
|

Efficacité et innocuité du plasma de convalescent en cas de forme grave de COVID-19, extrapolée de données relatives à d’autres formes graves d’infections respiratoires virales : revue systématique et méta-analyse

Abstract: P rès de 3 millions de personnes sur la planète ont reçu un diagnostic de maladie à coronavirus 2019 (COVID-19), et environ 0,2 million d'entre elles en sont décédées 1. De nombreux patients atteints de la COVID-19 développent des troubles respiratoires aigus sévères nécessitant une hospitalisa-tion aux soins intensifs et, souvent, une ventilation mécanique 2. Le taux de létalité de la COVID-19 pourrait être de 2,3 % chez l'ensemble des personnes ayant contracté le virus, et de 10 % à 40 % chez les personnes g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
(55 reference statements)
3
4
0
Order By: Relevance
“…There are four published systematic reviews on convalescent plasma that have shown that this treatment could reduce the mortality (24–27), but did not included only controlled trials and did not included the last study published by Libster (17). The current systematic review did not showed any benefit on the mortality reduction, consistent with other three published systematic reviews (28–30), while other systematic reviews were focused on other infectious diseases such as Ebola, influenza or SARS (3133), or other target populations (34).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There are four published systematic reviews on convalescent plasma that have shown that this treatment could reduce the mortality (24–27), but did not included only controlled trials and did not included the last study published by Libster (17). The current systematic review did not showed any benefit on the mortality reduction, consistent with other three published systematic reviews (28–30), while other systematic reviews were focused on other infectious diseases such as Ebola, influenza or SARS (3133), or other target populations (34).…”
Section: Discussionsupporting
confidence: 88%
“…Something that has been sufficiently proven before is that convalescent plasma administration does not have many severe adverse events in transfusion (1619,27,31). In contrast, more research is needed on the synergistic effect that plasma could have with other repositioning drugs, as has been demonstrated, for example, with the use of remdesivir as has been published in other studies (19,27,37).…”
Section: Discussionmentioning
confidence: 99%
“…Four published systematic reviews on convalescent plasma have shown that this treatment could reduce the mortality, 26 29 but did not include only controlled trials and did not include the last studies produced in Argentina by Libster et al 17 and Simonovich et al 22 The current systematic review did not show any benefit on the mortality reduction, consistent with other three published systematic reviews, 30 32 while other systematic reviews were focused on other infectious diseases such as Ebola, influenza, or SARS, 33 35 or other target populations. 36 …”
Section: Discussionsupporting
confidence: 75%
“…There is enough evidence proving that convalescent plasma administration does not have many severe adverse events in transfusion. 16 19 , 29 , 33 In contrast, more research is needed on the synergistic effect that plasma could have with other repositioning drugs, as has been demonstrated, for example, with the use of remdesivir, as has been published in other studies. 19 , 29 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…At that time, convalescent plasma was used by the U.S. military to treat flu patients. More recently, WHO approved it as an empiric treatment against Ebola virus infections in 2015, and it was deployed with success against the SARS (severe acute respiratory syndrome) in 2002-2003 and middle east respiratory syndrome in 2012 as well [10][11][12][13].…”
Section: Convalescent Plasmamentioning
confidence: 99%